CORPUS-BASED COMPARATIVE ANALYSIS OF AI TERMINOLOGY IN ENGLISH AND UZBEK - Nazarova Sevinchoy Umarbekovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: The fast pace of the Artificial Intelligence (AI) development has resulted in the appearance of an extremely large amount of specialized vocabulary, most of which is in English. The paper is a corpus-based comparative analysis of AI terminology in English and Uzbek that analyzes the usage patterns, translation strategies, and semantic adaptation. The study based on two similar corpora that are compiled using scholarly articles, news outlets, and online editions, finds main distinctions between frequency, lexical organization, and conceptual equivalence. The results show that English AI terms have a high standardization and frequency consistency, whereas Uzbek show a hybrid model of direct translation, transliteration, and borrowing. The paper mentions the difficulties of standardization of terminology and offers suggestions in the further linguistic and pedagogical evolution of Uzbek AI discourse.